Pattern Recognition and Computer Vision 5th Chinese Conference, PRCV 2022, Shenzhen, China, November 4-7, 2022, Proceedings, Part I - Yu, Shiqi; Zhang, Zhaoxiang; Yuen, Pong C.; Han, Junwei; Tan, Tieniu; Guo, Yike.; Lai, Jianhuang; Zhang, Jianguo (Cham : Springer International Publishing : Imprint: Springer, 2022)
The 4-volume set LNCS 13534, 13535, 13536 and 13537 constitutes the refereed proceedings of the 5th Chinese Conference on Pattern Recognition and Computer Vision, PRCV 2022, held in Shenzhen, China, in November 2022. The 233 full papers presented were carefully reviewed and selected from 564 submissions. The papers have been organized in the following topical sections: Theories and Feature Extraction; Machine learning, Multimedia and Multimodal; Optimization and Neural Network and Deep Learning; Biomedical Image Processing and Analysis; Pattern Classification and Clustering; 3D Computer Vision and Reconstruction, Robots and Autonomous Driving; Recognition, Remote Sensing; Vision Analysis and Understanding; Image Processing and Low-level Vision; Object Detection, Segmentation and Tracking.
Theories and Feature Extraction -- Architecture Colorization via Self-Supervised Learning and Instance Segmentation -- Dual-rank attention module for fine-grained vehicle model recognition -- Multi-View Geometry Distillation for Cloth-changing Person ReID -- Triplet Ratio Loss for Robust Person Re-identification -- TFAtrack:Temporal Feature Aggregration for UAV Tracking and A Unified Benchmark -- Correlated Matching and Structure Learning for Unsupervised Domain Adaptation -- Rider Re-identification Based on Pyramid Attention -- Temporal Correlation-Diversity Representations for Video-based Person Re-Identication -- FIMF Score-CAM: Score-CAM Based Visual Explanations via Fast Integrating Multiple Features of Local Space for Deep Networks -- Learning Adaptive Progressive Representation for Group Re-identification -- General High-Pass Convolution: A Novel Convolutional Layer for Image Manipulation Detection -- Machine learning, Multimedia and Multimodal -- Thangka Mural Line Drawing Based on Dense and Dual-Residual Architecture -- Self-Supervised Adaptive Kernel Nonnegative Matrix Factorization -- Driver Behavior Decision Making based on Multi-Action Deep Q Network in Dynamic Traffic Scenes -- Federated Twin Support Vector Machine -- Adversarial VAE with Normalizing Flows for Multi-Dimensional Classification -- Fuzzy Twin Bounded Large Margin Distribution Machines -- Harnessing Multi-Semantic Hypergraph for Few-Shot Learning -- Deep Relevant Feature Focusing for Out-of-Distribution Generalization -- Attributes based Visible-Infrared Person Re-identification -- A Real-Time Polyp Detection Framework for Colonoscopy Video -- Dunhuang Mural Line Drawing Based on Bi-Dexined Network and Adaptive Weight Learning -- Attention-based Fusion of Directed Rotation Graphs for Skeleton-based Dynamic Hand Gesture Recognition -- SteelyGAN: Semantic Unsupervised Symbolic Music Genre Transfer -- Self-Supervised Learning for Sketch-Based 3D Shape Retrieval -- Preference-aware Modality Representation and Fusion for Micro-video Recommendation -- Multi-Intent Compatible Transformer Network for Recommendation -- OpenMedIA: Open-Source Medical Image Analysis Toolbox and Benchmark under Heterogeneous AI Computing Platforms -- CLIP Meets Video Captioning: Concept-Aware Representation Learning Does Matter -- Attention-guided Multi-modal and Multi-scale fusion for Multispectral Pedestrian Detection -- XPNet: Cross-Domain Prototypical Network for Zero-Shot Sketch-Based Image Retrieval -- A high-order tensor completion algorithm based on Fully-Connected Tensor Network weighted optimization -- Momentum Distillation Improves Multimodal Sentiment Analysis -- Synthesizing Counterfactual Samples for Overcoming Moment Biases in Temporal Video Grounding -- Multi-Grained Cascade Interaction Network for Temporal Activity Localization via Language -- Part-based Multi-Scale Attention Network for Text-based Person Search -- Deliberate Multi-Attention Network for Image Captioning -- CTFusion: Convolutions Integrate with Transformers for Multi-modal Image Fusion -- Heterogeneous Graph-based Finger Trimodal Fusion -- Disentangled OCR: A More Granular Information for Text-to-Image" Retrieval -- Optimization and Neural Network and Deep Learning -- Cloth-Aware Center Cluster Loss for Cloth-Changing Person Re-identification -- Efficient Channel Pruning via Architecture-Guided Search Space Shrinking -- EFG-Net: A Unified Framework for Estimating Eye Gaze and Face Gaze Simultaneously -- Local Point Matching Network for Stabilized Crowd Counting and Localization -- Discriminative Distillation to Reduce Class Confusion in Continual Learning -- Enhancing Transferability of Adversarial Examples with Spatial Momentum -- AIA: Attention in Attention within Collaborate Domains -- Infrared and Near-Infrared Image Generation via Content Consistency and Style Adversarial Learning -- Adaptive Open Set Recognition with Multi-Modal Joint Metric Learning -- Prior-Guided Multi-Scale Fusion Transformer for Face Attribute Recognition -- KITPose: Keypoint-Interactive Transformer for Animal Pose Estimation -- Few-Shot Object Detection via Understanding Convolution and Attention -- Every Corporation Owns Its Structure: Corporate Credit Rating via Graph Neural Networks -- Unsupervised Image Translation with GAN Prior -- An adaptive PCA-like asynchronously deep reservoir computing for modeling data-driven soft sensors -- Double Recursive Sparse Self-Attention Based Crowd Counting In The Cluttered Background -- BiTMulV: Bidirectional-Decoding based Transformer With Multi-View Visual Representation for Image Captioning -- An improved lightweight network based on MobileNetV3 for palmprint recognition -- A Radar HRRP Target Recognition Method Based on Conditional Wasserstein VAEGAN and 1-D CNN -- Partial Least Square Regression via Three-factor SVD-type Manifold Optimization for EEG Decoding -- Single Deterministic Neural Network with Hierarchical Gaussian Mixture Model for Uncertainty Quantification -- Exploring Masked Image Modeling for Face Anti-Spoofing.
Keywords: Image processing-Digital techniques; Computer vision; Computer Imaging, Vision, Pattern Recognition and Graphics